Synthesis Methods, Performance Optimization, and Application Progress of Metal–Organic Framework Material MIL-101(Cr) - Jiayao Chen; Min Tang; Saiqun Nie; Pengcheng Xiao; Tian Zhao; Yi Chen (Chemistry, 2025)
MIL-101(Cr), a widely studied chromium-based metal–organic framework material consisting of chromium metal ions and terephthalic acid ligands, has attracted much attention due to its ultra-high specific surface area, large pore size, and excellent thermal, chemical, and aqueous stability. The outstanding properties and abundant unsaturated Lewis acid sites of this material have shown promising applications in aqueous phase adsorption, gas storage, separation, catalysis, drug delivery, and sensing. In this paper, we systematically review the synthesis technology and performance optimization strategy of MIL-101(Cr), discuss the advantages and limitations of various synthesis methods, such as traditional hydrothermal method, microwave-assisted hydrothermal method, template method, and solvent-thermal method, and summarize and analyze the optimization strategy of MIL-101 from the aspects of physical modification and chemical modification. In addition, this paper summarizes the latest application progress of MIL-101(Cr) in gas adsorption and separation, wastewater purification, pollutant removal, catalysis, and pharmaceutical delivery, and points out the current challenges and future development directions, to provide guidance and inspiration for the industrial application of MIL-101(Cr) and the development of new materials.